PENGUATAN IMPLEMENTASI PERMENDIKBUDRISTEK NO. 53 TAHUN 2023 PADA KURIKULUM DI UNIVERSITAS PGRI SILAMPARI - Samitra, Dian; Satinem, Satinem (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
The Indonesian government seeks to guarantee the quality of education and adapt competencies according to world changes by making policies and regulations. Regulation of the Minister of Culture, Research and Technology no. 53 of 2023 concerning quality assurance of higher education, is one of the regulations that mandates study programs to facilitate students to study outside the study program. Apart from that, in this regulation, study programs must prepare an integrated Program Learning Outcome (PLO). Therefore, this activity aims to strengthen the implementation of Regulation of the Minister of Culture, Research and Technology no. 53 of 2023 in the curriculum at PGRI Silampari University. The methods used in this activity include material exposure and mentoring. The results of the activities of the study program curriculum development team were able to prepare a PLO and curriculum map in accordance with Regulation of the Minister of Culture, Research and Technology no. 53 of 2023. The curriculum development team arranges activities outside the study program according to nine forms of learning activities in the hope of facilitating graduate competency.